2017
DOI: 10.1111/cpf.12484
|View full text |Cite
|
Sign up to set email alerts
|

Sphenopalatine ganglion stimulation induces changes in cardiac autonomic regulation in cluster headache

Abstract: In cluster headache patients subjected to low-frequency and sham stimulation of the sphenopalatine ganglion, we found changes indicating higher sympathetic tone during low-frequency stimulation preceding cranial autonomic symptoms or cluster pain. During cluster pain, regardless of stimulation parameters, we saw increased parasympathetic activity, congruent with previous reports. The results indicate involvement of cardiac autonomic regulation before and during cluster headache attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…With HRV measurements during cluster pain, induced by sphenopalatine ganglion stimulation, parasympathetic activity has been shown to increase, indicating the involvement of cardiac autonomic regulation, specifically TCR, in cluster headache mechanisms . Previously, beneficial effect of vagal stimulation in migraine has been reported .…”
Section: Discussionmentioning
confidence: 95%
“…With HRV measurements during cluster pain, induced by sphenopalatine ganglion stimulation, parasympathetic activity has been shown to increase, indicating the involvement of cardiac autonomic regulation, specifically TCR, in cluster headache mechanisms . Previously, beneficial effect of vagal stimulation in migraine has been reported .…”
Section: Discussionmentioning
confidence: 95%
“…The TCR is a powerful brainstem reflex that manifests as a sudden onset of hemodynamic influences on heart rate (HR); blood pressure (MABP) and has been associated with cardiac arrhythmias; asystole; apnea and gastric mobility [11]. It is an oxygen-conserving reflex that was first discovered in 1999 [12]; with considerable research ensuing [13][14][15][16][17]. The reflex may be activated by mechanical or chemical stimulation of the trigeminal nerve at any course along its distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also found a genetic commonalty in SB sufferers: a polymorphism of the HTR2A gene on chromosome [13][14][15][16][17][18][19][20][21][22][23][24][25]26]. This gene codes for 5-HT (serotonin) receptors in the brain and gut.…”
Section: Figurementioning
confidence: 99%
“…Among other functions, it supplies parasympathetic innervation to the brain's anterior vascular system, covering all the ipsilateral cerebral circulation in humans and bilaterally in rats [9]. Presently, SPG stimulation is used in humans for the treatment of cluster headaches, with trials showing safety and efficacy of an implantable microstimulator in the pterygopalatine fossa for this purpose [10][11][12].…”
Section: Introductionmentioning
confidence: 99%